Proteinogram of Immunized Sheep with Detoxified Tiyus serrulatus Scorpion Venom - Ferreira, Marina Guimarães; Michel, Ana Flávia Ribeiro; Reis, Lílian de Paula Gonçalves; Botelho, Ana Flávia Machado; Duarte, Clara Guerra; Chávez-Olórtegui, Carlos Delfin; Melo, Marília Martins (Acta Scientiae Veterinariae, 2022)
Background: Scorpionism is a worldwide medical issue, especially relevant in the tropical and subtropical countries. Tityus serrulatus is the species responsible for most cases in Brazil. Antivenom administration to victims is the sole specific therapy obtained from donor animals. Most of these donors suffer with symptoms of the poisoning, debilitating their health and reducing their life expectancy. The aim of the present research was to evaluate whether the immunogens prepared from the crude and detoxified venom of T. serrulatus promoted different changes in fractionated sheep plasma proteins, during a scorpion antivenom serum production. Materials, Methods & Results: Twelve sheep, healthy, mean weight of 30 kg, were distributed into 3 groups (n = 4): G1 (control), G2 (crude venom) and G3 (detoxified venom). The adopted immunization protocol (first cycle) had 6 doses, 3 using Freund's adjuvant, with a 21-day interval between each one (day 0, 22 and 43), and 3 doses with no adjuvant (booster) and 0.2 mg of antigen (reinforcement), spaced 3 days between each other (day 50, 53 and 56). Group control (G1) received 6 immunizations with phosphate buffered saline (PBS) associated with Freund's adjuvant (1:1), while the other 2 groups received 0.5 mg of venom (G2) and detoxified venom (G3), respectively, diluted in PBS, associated with the Freund adjuvant. The boosters were 1/3 of the initial dose, diluted only PBS. At baseline (T0) and at 24 and 48 h after immunization, all animals underwent clinical examinations. Blood samples were collected at day 0, 22, 43, 53 and 56 for proteinogram analysis. Total protein, albumin and globulins fractions were measured. Plasma albumin concentration at T0 ranged from 3.41-4.86 g/dL, with a mean value of 4.12 g/dL. There was no statistical difference between the 3 experimental groups. The normal values determined for α-globulin range from 0.14 to 0.54 g/dL, with a mean of 0.31 g/dL (T0). There was a significant increase in the 3rd immunization and its respective interval (24-48 h), with values above normal in all groups: G1 (0.66 g/dL), G2 (0.62 g/dL) and G3 (0.65g/dL). The β-globulin was subdivided into β1 and β2 globulin. At T0, the normal values of β1 ranged from 0.45 to 1.05 g/dL, with a mean of 0.664 g/dL, and no significant change was observed in this classification. On the other hand, there was an abrupt increase in β2 in all groups after the first immunization, compared to the baseline value in T0 (0.37 g/dL mean value). From the third to the 6th immunization, there was an important reduction in β2 fraction when compared with baseline value. The γ-globulins fraction ranged from 0.80 g/dL to 76 g/dL. In the 6th immunization, there was a significant difference between G1 and the groups that received venom (G2 and G3). Therefore, all animals presented an acute inflammatory response, evidenced by the significant reduction of plasma albumin and an increase in α-globulin and β2-globulin. It is important to point out that T. serrulatus detoxified venom did not cause alterations in ovine proteinogram during the first cycle of immunization. Discussion: The fact that both groups (G2 and G3) presented acute inflammatory response, indicates that this alteration is caused by the adjuvant present in the immunization protocol. Tityus serrulatus venom detoxified with glutaraldehyde did not ~cause significant alterations in ovine proteinogram in the early stages, suggesting that itmay be used as an alternative antigen for the production of antivenom, improving clinical conditions of donor animals. Keywords: scorpion, clinical pathology, ruminants, inflammation, antiserum. Título: Proteinograma de ovelhas imunizadas com veneno detoxificado do escorpião Tityus serrulatus Descritores: escorpião, patologia clínica, ruminantes, inflamação, antisoro.